PEMANFAATAN ENTERPRISE ARCHITECTURE PLANNING UNTUK PERENCANAAN STRATEGIS SISTEM INFORMASI - Surendro, Kridanto (Institute of Research and Community Outreach - Petra Christian University, 2007)
In the endeavor to attain its goal, an enterprise strives to undertake challenges and changes of which strategies for effective measures and efficient resource usage become necessary. To this necessity, the role of information system for supporting and enhancing enterprise performance has become more strategic and widely established. This elicits mission for information system and advises a general course of action to give a unified direction for planning, implementation and control in alignment with enterprise business strategy. A planning that identifies enterprise's information requirement and possible innovations in technology utilization for enhancing enterprise performance is a first step to begin the fulfillment of information system mission. Such a planning can be satisfied by employing Enterprise Architecture Planning methodology, which is purposed to deliver data architecture, application architecture, technology architecture and implementation plan. Implementation plan is comprised of a sequence of application development and technology platform migration / acquisition. Such a sequence is elaborated further according to business aspect as a main drive, organizational aspect which addresses people who will be involved in implementation, information system and information technology environment aspect as an interface for existing and future systems, and application development aspect which interconnects one stage in the development sequence with another. Abstract in Bahasa Indonesia : Pencapaian tujuan suatu enterprise menghadapi berbagai tantangan serta perubahan yang memerlukan strategi untuk langkah-langkah efektif dan pemanfaatan sumber daya yang efisien. Salah satu strategi yang penting dan semakin banyak digunakan adalah pemanfaatan dan peningkatan dukungan sistem informasi bagi enterprise. Penerapan strategi ini mengembankan misi pada sistem informasi yang pemenuhannya memerlukan keterpaduan arah dalam perencanaan, pelaksanaan dan pengendalian yang selaras dengan strategi bisnis enterprise. Pembangunan strategi untuk pemenuhan misi sistem informasi dimulai dari perencanaan yang mengidentifikasi kebutuhan informasi dan kemungkinan inovasi pemanfaatan teknologi untuk peningkatan kinerja enterprise. Perencanaan ini dapat memanfaatkan metodologi Perencanaan Arsitektur Enterprise yang menghasilkan arsitektur data, arsitektur aplikasi, arsitektur teknologi, dan arah rencana implementasinya bagi enterprise. Rencana implementasi berupa urutan pengembangan aplikasi dan migrasi / akuisisi landasan teknologi dielaborasikan menurut aspek bisnis sebagai pendorong utama, aspek organisasional untuk penentuan peran bagi sumber daya pelaku implementasi, aspek lingkungan sistem informasi dan teknologi informasi untuk menjembatani kondisi sistem-sistem saat ini dan yang akan diwujudkan, serta aspek pengembangan aplikasi yang mempertautkan satu tahap pengembangan dengan tahap pengembangan lainnya. Kata kunci: rencana strategis, sistem informasi, EAP, Zachman Framework.